2022
DOI: 10.3390/diagnostics12092250
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Endometritis in Infertile Women: Impact of Untreated Disease, Plasma Cell Count and Antibiotic Therapy on IVF Outcome—A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis aims to evaluate the impact of chronic endometritis (CE) and its therapy on in vitro fertilization (IVF) outcome. Additionally, we aim to investigate whether various degrees of CE severity may exert a different effect on IVF outcome. Ongoing-pregnancy rate/live-birth-rate (OPR/LBR), clinical-pregnancy rate (CPR), and miscarriage rate (MR) were calculated. A total number of 4145 patients (from ten studies) were included. Women with CE had lower OPR/LBR (OR 1.97, p = 0.02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 56 publications
2
24
0
4
Order By: Relevance
“…Nevertheless, our data and analysis demonstrates that hysteroscopic CE plays an important role in predicting IVF pregnancy outcomes. According to previous literature, endometrial plasma cells do not predict pregnancy outcomes at low levels, 34 and IVF success may be affected only by severe, and not mild, CE 35 . Considering this, patients with hysteroscopic CE in our study seemed to have greater severity of CE compared to patients with histopathologic CE.…”
Section: Discussionsupporting
confidence: 39%
“…Nevertheless, our data and analysis demonstrates that hysteroscopic CE plays an important role in predicting IVF pregnancy outcomes. According to previous literature, endometrial plasma cells do not predict pregnancy outcomes at low levels, 34 and IVF success may be affected only by severe, and not mild, CE 35 . Considering this, patients with hysteroscopic CE in our study seemed to have greater severity of CE compared to patients with histopathologic CE.…”
Section: Discussionsupporting
confidence: 39%
“…In a meta-analysis of eight studies, Vitagliano et al [ 40 ] demonstrated a lower OPR/LBR (OR = 1.97, 95% CI = 1.11–3.48, p = 0.02) and CPR (OR = 2.28, 95% CI = 1.34–3.86, p = 0.002) in infertile women with CE than in those without CE (defined as ≥1 CD138(+)-ESPC in 1 HPF = 10 ESPCs in 10 HPFs), whereas there was no difference in the MR. Additionally, a subgroup analysis of two studies disclosed that severe CE (defined as ≥50 ESPCs in 10 HPFs) was associated with poor reproductive outcomes (OPR/LBR: OR = 0.43, 95% CI = 0.25–0.74, p = 0.003, and CPR: OR = 0.40, 95% CI = 0.24–0.68, p = 0.0007) compared to mild CE (defined as 10–40 CD138(+) ESPCs in 10 HPFs), but again, without any difference in the MR. By contrast, there was no difference between mild CE and non-CE in terms of the OPR/LBR, CPR, and MR.…”
Section: Challenges In Clinical Diagnosis Of Histopathologic Cementioning
confidence: 99%
“…Предложены различные теории для объяснения связанных с ХЭ нарушений рецептивности эндометрия, включая активацию местных воспалительных процессов с измененной секрецией цитокинов (ЦК) и хемокинов, аномальную лейкоцитарную инфильтрацию эндометрия, измененную сократимость матки, нарушения децидуализации и васкуляризации эндометрия [10]. Однако, как отмечают эксперты, несмотря на «интригующий» характер этих теорий, имеющиеся данные о корреляции между ХЭ и дефектами имплантации преимущественно основаны на данных исследований с определенными недостатками (гетерогенный дизайн, различные критерии диагностики ХЭ и др.…”
Section: Introductionunclassified
“…Однако, как отмечают эксперты, несмотря на «интригующий» характер этих теорий, имеющиеся данные о корреляции между ХЭ и дефектами имплантации преимущественно основаны на данных исследований с определенными недостатками (гетерогенный дизайн, различные критерии диагностики ХЭ и др. ), и, таким образом, научное сообщество остается разделенным на тех, кто за и против того, чтобы признать, что ХЭ является реальной причиной женского бесплодия [10].…”
Section: Introductionunclassified
See 1 more Smart Citation